Derivation of some translation-invariant lindblad equations for a quantum Brownian particle - De Roeck, Wojciech; Spehner, Dominique (Journal of statistical physics, 2013)
We study the dynamics of a Brownian quantum particle hopping on an inﬁnite lattice with a spin degree of freedom. This particle is coupled to free boson gases via a translation-invariant Hamiltonian which is linear in the creation and annihilation operators of the bosons. We derive the time evolution of the reduced density matrix of the particle in the van Hove limit in which we also rescale the hopping rate. This corresponds to a situation in which both the system-bath interactions and the hopping between neighboring sites are small and they are effective on the same time scale. The reduced evolution is given by a translation-invariant Lindblad master equation which is derived explicitly.
Published online: 14 December 2012
Gesehen am 29.11.2018